Søren Bisgaard's contributions to Quality Engineering: Design of experiments. Issue Volume 31:Issues 1(2019) (2nd January 2019) - Vining, Geoff
Abstract: This article examines Søren's impact on the design and analysis of experiment through three of his published articles in ASQ journals. These articles demonstrate Søren's unique blend of engineer and statistician with the ability to see the big picture both of the solution to the specific problem and of the solution strategy for good practice. Søren was a giant in our field who was struck down too early in life by mesothelioma at the age of 58 years. His work, and more importantly his impact on his colleagues, has continued to influence the profession.